Correlation of Blood Biomarkers with Age Informs Pathomechanisms in Succinic Semialdehyde Dehydrogenase Deficiency (SSADHD), a Disorder of GABA Metabolism - Jansen, EE (J Inherit Metab Dis, 2016)
We hypothesized that blood levels of GABA and γ-hydroxybutyric acid (GHB), biomarkers of succinic semialdehyde dehydrogenase deficiency (SSADHD), would correlate with age. GABA and GHB were quantified in plasma and red blood cells (RBCs) from eighteen patients (age range 5–41 years; median 8). Both metabolites negatively correlated with age (P<0.05). Plasma and RBC GHB declined with age, reaching a nadir and approximate steady-state by 10 years. Declining plasma GABA achieved this approximate steady state at 30–40 years of age. These biomarker relationships may reflect further GABA- and GHB-ergic neurotransmission imbalances that correlate with the onset of adolescent/adulthood neuropsychiatric morbidity and epilepsy in SSADHD.